(untitled) (Fiep Bulletin - online, 2013)
Guideline, as activity, follows the man from his home. However, as sport has emerged in the Nordic countries for over a hundred years, with the aim of carrying out a physical activity outdoors, keeping the mind busy practicing throughout their implementation and contributing to environmental education. The study is in respect of that guidance can be inserted into the Physical Education School, because it has characteristics that contribute teaching in a positive and stimulating the development of the student. Today, because to be an important tool interdisciplinary and able to develop qualities bio-psycho-social importance in the process of human development, many schools apply this method is to seek better quality in education.